Pembuatan Strategy Farming Game Berbasis Flash - Haryanto, Haryanto; Purba, Kristo Radion; Gunadi, Kartika (Jurnal Infra, 2016)
Game is an activity to find a new challenge or for having fun. Game have several genres like farming game, simulation, strategy, action, and many more. Each tipe has its own advantage and disadvantage like strategy genre is usually more challenging because its rather difficult hand have to stay focus to win. But other game like farming game is very fun but fell not challenging enough because usually farming game is very easy to play.Because of the difficulty reason, this game with farming and strategy genre have enemy that will attack the plants. Player also can protect the plants by killing enemy or by buying a tower that can attack enemy otomatically when an enemy come closer to the plants around that tower. This game is made by using Adobe Flash Professional CS6.From questionnaire average score 7.4, proofing that game with farming and strategy genre will become an interesting game that can be played.